Bibliometric Analysis of Nano-Sized Agricultural Waste Brake Pads Research During 2018-2022 Using VOSviewer (Unijourn Publisher, 2022)
The agricultural brake pad is one solution to reduce the danger of using asbestos in-vehicle systems. This research aims to conduct bibliometric analysis in nano-sized agricultural waste brake pads by combining mapping analysis using VOSviewer software. Application reference manager used to obtain research data. The data received results from a search based on the keyword “Brake pads, Nano-sized, Agricultural waste.” The search results found 1000 relevant published articles in 2018-2022. The results showed that research on nano-sized agricultural waste brake pads has been increasing through the year, and research continues with a high number of publications in early 2022. This study demonstrates the importance of bibliometric analysis in analyzing data on what phenomena happen. This research is expected to help and become a reference for researchers in conducting and determining the research themes.